A zwitterionic (poly)methacrylate monolitic capillary column with dual HILIC – reversed-phase mechanism for uni- and two-dimensional HPLC - Staňková, Magda; Jandera, Pavel (University of Pardubice, 2017)
Sulfobetaine zwitterionic monolithic columns were synthesized by in-situ polymerization (in fused silica capillaries) of a N,N-dimethyl-N-metacryloxyethyl- N-(3-sulfopropyl) ammonium betaine (MEDSA) functional monomer in combination with different cross-linking monomers. From among the ten crosslinkers tested, bisphenol A glycerolate dimethacrylate provides monolithic capillary columns with best chromatographic efficiency (60 000-70 000 theoretical plates per meter). The respective columns show excellent column-tocolumn reproducibility of pore morphology, separation selectivity, good permeability and low mass transfer resistance, so that being suitable for fast and selective separation of various samples. Monolithic sulfobetaine polymethacrylate (BIGDMA-MEDSA) micro-columns designed in our laboratory exhibit a dual retention mechanism, in acetonitrile-rich mobile phase, polar (hydrophilic) interactions control the retention (HILIC separation mode), whereas in more aqueous mobile phases the column shows essentially non-polar with a major role of hydrophobic interactions properties (reversed-phase, RP mode). The dual-mode retention mechanism was investigated and applied to the HILIC and reversedphase HPLC separations of barbiturates, sulfonamides, nucleobases, nucleosides, phenolic, and other carboxylic acids, polyphenols, flavonoids plus other lowmolecular compounds. The separation selectivities in the HILIC and RP dimensions are highly complementary to each other, so that a zwitterionic sulfobetaine polymethacrylate micro-column can be used in the first dimension of two-dimensional LC in alternating RP and HILIC modes, coupled with a short (3- 5 cm) alkyl-bonded core-shell or silica-based monolithic column in the second dimension, for HILIC×RP and RP×RP comprehensive two-dimensional separations. During the HILIC×RP period, a programme with the decreasing acetonitrile gradient is used for separation in the first dimension, so that at the end of the gradient the polymeric monolithic micro-column is equilibrated with a highly aqueous mobile phase and is ready for repeated sample injection, in this case, for separation under reversed-phase gradient conditions with the increasing concentration of acetonitrile in the first dimension.